2001
DOI: 10.2472/jsms.50.883
|View full text |Cite
|
Sign up to set email alerts
|

Structural Materials. Flexural and Shear Behavior of Reinforced Concrete Beams Damaged by Alkali-Silica Reaction under Reversed Cyclic Loads.

Abstract: Flexural and shear behavior of reinforced concrete beams damaged by alkali-silica reaction (ASR) was investigated under monotonous and reversed cyclic loads, mainly focused on the shear resistant mechanism after flexural yielding. In case under the monotonous loads, shear capacity of the beams damaged by ASR was rather increased by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…(7) predict that the tensile forces on stirrups will significantly increase after the occurrence of diagonal shear crack in the shear span zone represented by V c . This tendency has been documented in another experimental study as reported in [6]. Also Fig.…”
Section: Test Results and Discussionsupporting
confidence: 82%
“…(7) predict that the tensile forces on stirrups will significantly increase after the occurrence of diagonal shear crack in the shear span zone represented by V c . This tendency has been documented in another experimental study as reported in [6]. Also Fig.…”
Section: Test Results and Discussionsupporting
confidence: 82%
“…A hollow beam has a longitudinal void along its span caused by the removal of concrete using lightweight void formers such as Polyvinyl Chloride (PVC) pipes (Joy and Rajeev, 2014;Varghese and Joy, 2016;Ragavi, 2017;Dhinesh and Satheesh, 2017;Al-Gasham, 2015;Ngu, 2017;Parthiban and Neelamegam, 2017), Polystyrene foams (Manikandan et al, 2015), Polypropylene plastic sheets (Kumbhar and Jadhav, 2018) and plastic bottles (Mathew and Varghese, 2016;Sariman and Nurdin, 2018). These beams have been reported to generally offer a lower strength compared to the solid ones (Kumbhar and Jadhav, 2018;Al-Gasham, 2015;Alshimmeri and Al-Maliki, 2014;Alnuaimi et al, 2008;Inoue and Egawa, 1996). This was associated with the changes caused by the void in its cross-sectional configuration which reduces its second moment of inertia and affects its strength (Ngu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that these hollow member does not have sufficient plastic deformation to absorb the applied energy. Therefore, in order to ensure the safety of these elements, many investigations should be made upon it (Susumu et al 1996) [1]. So In the present research, a new type of composite section was developed; this section is completely different from the composite sections studied in previous research.…”
Section: Introductionmentioning
confidence: 93%